A review of the studies investigating the effects of noise exposure on humans from 2017 to 2022: Trends and knowledge gaps - SheikhMozafari Mohammad Javad; Omari Shekaftik Soqrat; Fasih Ramandi Fatameh; Monazzam Esmaeelpour Mohammad Reza; Biganeh Jamal (Noise Mapping)
Due to rapid urbanization and industrialization, noise pollution has become a growing global concern, with significant impacts on occupational and environmental health. Unlike earlier times when it received limited attention, its importance has increased due to mounting evidence of its health effects. Research on noise pollution highlights its consequences and helps identify gaps that require further exploration. This systematic review aims to compile and categorize the health effects associated with various sources of noise pollution.